Pengabdian St. Mansyur (1915-1968) Sebagai Guru Surau, Imam Mesjid, dan Imam Tentara dalam Perspektif Pendidikan Islam - Wisber Wiryanto (Prodi Pendidikan Keagamaan Islam, 2022)
St. Mansyur (1915-1968) was born in the village of Guguktinggi, Agam. He is a graduate of the Sumatra Thawalib Madrasah, Padang Panjang, he is a teacher, mosque imam, and army priest who has a hierarchical relationship with RE Martadinata and Bahrum Rangkuti figures who have research. However, the history has not been studied, so it is necessary to conduct a study. The research was conducted by considering the figure of St. Mansyur meets the criteria of popularity, influence, controversy, uniqueness, integrity, relevance, and contribution of his thoughts. The results showed that St. Mansyur as a surau teacher, mosque priest, and army priest worked with individuals and society with his diligence and expertise as a form of charity with knowledge and faith. He contributed ideas about the concept of devotion as a surau teacher, mosque imam, and army imam which are forms of the profession in the perspective of Islamic education. St. Jobs Mansyur as a surau teacher, mosque imam and army imam are forms of the Islamic education profession that are taken in stages through a step-by-step process in accordance with increasing expertise and work experience. Devotion St. Mansyur as a surau teacher, mosque imam and army imam in the perspective of Islamic education is a portrait of the profession of the past; Among the forms of attitude and behavior that are still relevant to the present need to be used as a reference.